2008
DOI: 10.1007/s10661-007-0146-9
|View full text |Cite
|
Sign up to set email alerts
|

Contamination from historic metal mines and the need for non-invasive remediation techniques: a case study from Southwest England

Abstract: The UK is legally required by the EU Water Framework Directive (WFD) to improve the environmental quality of inland and coastal waters in the coming years. Historic metal mine sites are recognised as an important source of some of the elements on the WFD priority chemicals list. Despite their contamination potential, such sites are valued for their heritage and for other cultural and scientific reasons. Remediating historic mining areas to control the contamination of stream waters, whilst also preserving the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Total metal concentrations measured in the sediment samples (Table A6 supplementary material) were comparable with previous research by Rieuwerts et al (2009), who reported mean concentrations of Pb and Zn equal to 2,909 mg kg -1 and 564 mg kg -1 respectively.…”
Section: Sediment Concentrationssupporting
confidence: 88%
See 2 more Smart Citations
“…Total metal concentrations measured in the sediment samples (Table A6 supplementary material) were comparable with previous research by Rieuwerts et al (2009), who reported mean concentrations of Pb and Zn equal to 2,909 mg kg -1 and 564 mg kg -1 respectively.…”
Section: Sediment Concentrationssupporting
confidence: 88%
“…Pirrie et al, 2003;Rieuwerts et al, 2014;Hudson-Edwards et al, 1996). For example, in many areas of the UK, such as southwest England and other parts of Europe, evidence of uncontrolled historic mining activities has shown to have a large and lasting impact (Galan et al, 2003;Nieto et al, 2006;Rieuwerts et al, 2009). Discharge of metal rich water from abandoned mines to surface and groundwater, and contamination of soils and sediments through associated industrial activity are among the highest recorded in the UK.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Working Party, 1978), based on species' tolerance to acidity and metal 769 contamination, has also been suggested (Gray and Delaney, 2008) and somesuccess has been achieved using a multi-metric approach by considering 771 multiple biological metrics simultaneously (e.g., Clews and Ormerod, 2009 More subtle community alterations as a result of physiological or behavioural 780 changes are less easy to diagnose (Younger and Wolkersdorfer, 2004) (Table 781 3). For example, Petersen and Petersen (1983) Clements et al (1989) reported that high copper doses increased predation 792 pressure, so much that the numbers of caddisfly, mayfly and chironomids 793 were dramatically reduced. Maltby and Naylor (1990) can be concentrated or magnified in the food chain (Sola et al, 2004) (Table 841 3).…”
Section: Hydrological Impacts 555mentioning
confidence: 99%
“…Active and abandoned mines are a major source of contamination for both terrestrial and aquatic environments 1 . Water pollution from these mines can originate from point sources such as mine adits, or diffuse sources such as spoil heaps 2 . In the UK, the potential contamination by mines is compounded by the fact that owners of mines abandoned before 1999 bear no responsibility for their impacts.…”
Section: Introductionmentioning
confidence: 99%